SAbDab: the structural antibody database - Dunbar, J; Krawczyk, K; Leem, J; Baker, T; Fuchs, A; Georges, G; Shi, J; Deane, C (Oxford University Press, 2014)
Structural antibody database (SAbDab; http://opig.stats.ox.ac.uk/webapps/sabdab) is an online resource containing all the publicly available antibody structures annotated and presented in a consistent fashion. The data are annotated with several properties including experimental information, gene details, correct heavy and light chain pairings, antigen details and, where available, antibody–antigen binding affinity. The user can select structures, according to these attributes as well as structural properties such as complementarity determining region loop conformation and variable domain orientation. Individual structures, datasets and the complete database can be downloaded.